Brand Loyalty and Switching: An Empirical Study on Mobile Phone Usage Among Young Indian Adults - Nandi, Shampa; Pattanayak, J. K. (Indian Journal of Marketing, 2015)
Mobile phones are emerging like a boon quench for providing facilities, which are beyond the common man’s imagination. The mobile phone industry is growing at an incredible pace with no sign of a slowdown, and the Indian mobile market is one of the fastest growing markets in the world. Cell phones are a pervasive new communication technology, especially among young people. The youth have a unique behaviour compared to the older generations, with research showing that a lot of what they purchase represents their self-expression. Mobile devices are a part of their personal selves and are a vital component which connects them with the world and the people around them. The present study focused on the brand switching tendencies of young Indians and effectively analyzed the impact of different demographic variables on brand loyalty. A total number of 600 young adults comprising of both students and working professionals from various reputed colleges and companies in Bangalore were surveyed and their responses were analyzed using SPSS 20. The study indicated that Apple has the most loyal base of customers, though Samsung is the most popular brand, and among the various demographic factors, only age had an impact on brand loyalty. Technical incompatibility and new technical and value added features are the primary reasons for switching to a new handset.